The Effect of The Height of a Second-Degree Relative on Children with Short Stature - Seda Yilmaz Semerci; Hasan Onal; Neval Topal; Rengin Siraneci (Trends in Pediatrics, 2021)
Objective: This study aimed to investigate the effect of the heights of second-degree relatives on adult height.